2022
DOI: 10.1007/s10796-022-10287-0
|View full text |Cite
|
Sign up to set email alerts
|

The Source of SMEs’ Competitive Performance in COVID-19: Matching Big Data Analytics Capability to Business Models

Abstract: Literature notes that firms are keen to develop big data analytics capability (BDAC, e.g. big data analytics (BDA) management and technology capability) to improve their competitive performance (e.g. financial performance and growth performance). Unfortunately, the extant literature has limited understanding of the mechanisms by which firms’ BDAC affects their competitive performance, especially in the context of small and medium-sized enterprises (SMEs). Using resource capability as the theoretical lens, this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 96 publications
0
18
0
1
Order By: Relevance
“…However, the results also show that the effects of applying each type of analytics are different. Song et al (2022) found that COVID-19 has positive moderating effects on the relationship between big data analytics management capability and value attributes of business models.…”
Section: Papers In This Special Issuementioning
confidence: 97%
“…However, the results also show that the effects of applying each type of analytics are different. Song et al (2022) found that COVID-19 has positive moderating effects on the relationship between big data analytics management capability and value attributes of business models.…”
Section: Papers In This Special Issuementioning
confidence: 97%
“…The pretest responses are not used in the analysis. Following the pretest, data were gathered through an online survey of midlevel executives, analytics professionals, managers, vice presidents, presidents, CEOs, and founders since they are considered to be the most knowledgeable of their organizations' BDA efforts [13], [60], [61] and have been used in prior influential BDA research (e.g., [1], [7], [9], [13], [27], [45]). A leading national Canadian market research firm with a very large panel of business entities and executives was contracted to collect the data.…”
Section: A Datamentioning
confidence: 99%
“…Another environmental factor that drove technological transformation in SMEs is disruptions, such as the COVID-19 crisis, which have received increasing academic attention within the last 2 years (e.g. Song et al 2022;Musa et al 2022;Akpan et al 2022). In this context, technology was a survival source during the pandemic, as companies adopted digital technologies to maintain their operations (Akpan et al 2021;Priyono et al 2020).…”
Section: Drivers Of Technological Transformationmentioning
confidence: 99%